Anatomical distribution of bronchoalveolar lavage fluid as assessed by digital subtraction radiography. Issue 8 (August 1987) - Kelly, C A; Kotre, C J; Ward, C; Hendrick, D J; Walters, E H
Abstract : A digital subtraction imaging technique was used to visualise directly the anatomical distribution of 3 X 60 ml aliquots of saline containing a low concentration of radio-opaque dye, introduced sequentially into a segment of the middle lobe. It was possible to estimate the relative movement of fluid within the segment during the sequential aspiration of each of these aliquots. The first 60 ml aliquot introduced stayed close to the bronchoscope and probably sampled only the proximal airways. With the introduction of cumulative volumes of 120 ml or more, the fluid filled the segment more evenly. Aspiration then moved fluid back from the periphery, implying that the aspirate had also lavaged both distal airways and alveoli.